SCALING SOCIAL VALUE THROUGH CREATIVE TECHNOLOGIES: STRATEGIC CHALLENGES IN DIGITAL ENTREPRENEURSHIP - Lim, Sofia; Tan, Jaden; Scott, James; Arisa, Ma'rifani Fitri (Journal of Social Entrepreneurship and Creative Technology, 2026)
The rapid expansion of creative technologies has transformed digital entrepreneurship into a critical driver of social innovation and inclusive growth. Platform ecosystems, artificial intelligence, and data-driven infrastructures enable ventures to scale rapidly, yet strategic tensions emerge between technological acceleration and sustained social mission integrity. This study aims to develop and empirically validate a strategic framework explaining how digital entrepreneurs scale social value while navigating governance, stakeholder, and measurement challenges. A mixed-methods explanatory sequential design was employed, combining survey data from 214 digital social ventures with in-depth case studies of selected firms operating in technology-intensive sectors. Multiple regression and structural equation modeling were used to test relationships among technological capability, strategic agility, stakeholder integration, impact measurement sophistication, and scaling performance. Findings indicate that technological capability significantly predicts scaling performance (? = 0.41, p < 0.001), with strategic agility acting as a mediating variable. Hybrid ventures balancing innovation with governance and ecosystem collaboration achieved superior scaling outcomes. The study concludes that sustainable scaling of social value requires multidimensional capability alignment rather than technology-driven expansion alone. Integrative strategic management of creative technologies is essential for maintaining legitimacy, adaptability, and measurable social impact in digital entrepreneurship.